Perception of traumatic childbirth of women, influencing factors and its relationship with post-traumatic stress disorder - Wei, Weiwei; Feng, Xiaoyan; Qin, Hong; Yang, Xiaochang (Frontiers in Public Health, 2025)
ObjectivesSome of individuals with psychological birth trauma (PBT) develop into postpartum post-traumatic stress disorder (PP-PTSD) further. Study investigated the prevalence and influencing factors of PBT and its correlation with PP-PTSD, to fill the literature gap in the prevention of postpartum related psychological birth trauma.MethodsA total of 306 women who gave birth vaginally from Chongqing, China participated in this study. Pregnant women filled the basic information when they entered the delivery room and waited for delivery. The psychological birth trauma and posttraumatic stress scales were completed during 1–3 days postpartum. Information on labor and delivery outcomes is available in the hospital's electronic medical record. Variation analysis and Pearson correlation were used on the influencing factors of PBT and the correlation with PP-PTSD.ResultsThe median PBT score of the subjects in this study was 41 points; the incidence rate of PTSD (scores greater than 38) is 5%, with an average score of (22.38 ± 7.126). All dimensions of PBT positively correlated with post-traumatic stress disorder, respectively. Lower score of perceived PBT is associated with work, exercise and learning about delivery; is also associated with less vaginal examinations, the use of pain relief and doula accompaniment.ConclusionThis study suggests that every dimension of PBT should be taken seriously to prevent PP-PTSD. Work, exercise and learning about delivery during pregnancy may be promising protective factors for perceived PBT; the use of pain relief or doula accompaniment are still effective ways to Improve the delivery experience.